1999
DOI: 10.1016/s0370-2693(98)01464-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of the ABC enhancement in the reaction

Abstract: The d d → α X 0 reaction at beam energies close to the η threshold shows very strong structure in the missing mass corresponding to the ABC enhancement. The deuteron tensor analysing power A yy , and the slope of the vector analysing power A y with respect to angle, have been measured for this reaction around the forward direction. Both signals are small, and their variations with the α-particle momentum are in broad agreement with a theoretical model in which each pair of nucleons in the projectile and target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Subsequent measurements showed that this enhancement also persists in the fusion reactions to d and 4 He [18][19][20][21][22][23][24][25][26][27][28], if the produced pion pair is of isoscalar nature. Since there was no plausible explanation for this effect, it got named after the initials of the authors of the first publication on that issue.…”
Section: Abc Effectmentioning
confidence: 99%
“…Subsequent measurements showed that this enhancement also persists in the fusion reactions to d and 4 He [18][19][20][21][22][23][24][25][26][27][28], if the produced pion pair is of isoscalar nature. Since there was no plausible explanation for this effect, it got named after the initials of the authors of the first publication on that issue.…”
Section: Abc Effectmentioning
confidence: 99%
“…Its explanation has been a puzzle since then. In subsequent bubble-chamber [2,3] and single-arm magnetic spectrometer measurements [4][5][6][7][8][9][10][11][12] this enhancement was observed also in double-pionic fusion reactions leading to d, 3He, and 4He, if an isoscalar pion pair was produced. However, such an enhancement was not observed in fusion reactions leading to deuteron and triton, if an isovector pion pair was produced.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it has been named just after the initials of those authors. In subsequent bubble-chamber [2,3] and single-arm magnetic spectrometer measurements [4][5][6][7][8][9][10][11] this enhancement showed up in double-pionic fusion reactions leading to d, 3 He and 4 He, if an isoscalar pion pair was produced. However, such an enhancement was not observed in fusion reactions leading to deuteron and triton, if an isovector pion pair was produced.…”
Section: Introductionmentioning
confidence: 99%